Distinct evolution and dynamics of epigenetic and genetic heterogeneity in acute myeloid leukemia - Li, Sheng; Garrett-Bakelman, Francine E; Chung, Stephen S; Sanders, Mathijs A; Hricik, Todd; Rapaport, Franck; Patel, Jay; Dillon, Richard; Vijay, Priyanka; Brown, Anna L; Perl, Alexander E; Cannon, Joy; et al. (Nature medicine, 2016)
Genome-wide methylome sequencing of serial samples obtained from patients with acute myeloid leukemia reveals that epigenetic alleles and genetic alleles follow independent courses during disease evolution. Genetic heterogeneity contributes to clinical outcome and progression of most tumors, but little is known about allelic diversity for epigenetic compartments, and almost no data exist for acute myeloid leukemia (AML). We examined epigenetic heterogeneity as assessed by cytosine methylation within defined genomic loci with four CpGs (epialleles), somatic mutations, and transcriptomes of AML patient samples at serial time points. We observed that epigenetic allele burden is linked to inferior outcome and varies considerably during disease progression. Epigenetic and genetic allelic burden and patterning followed different patterns and kinetics during disease progression. We observed a subset of AMLs with high epiallele and low somatic mutation burden at diagnosis, a subset with high somatic mutation and lower epiallele burdens at diagnosis, and a subset with a mixed profile, suggesting distinct modes of tumor heterogeneity. Genes linked to promoter-associated epiallele shifts during tumor progression showed increased single-cell transcriptional variance and differential expression, suggesting functional impact on gene regulation. Thus, genetic and epigenetic heterogeneity can occur with distinct kinetics likely to affect the biological and clinical features of tumors.